Manajemen Waktu Program Pembelajaran Tahfidz Al-Quran di Pondok Pesantren Tahfidz Maskanul Huffadz Medan - Yunda Sakinah; Ibrahim Hasan (LP. Ma'arif Janggan Magetan, 2024)
Time management in education is very important so that the goals you want to target can be easily achieved and systematically. If there is no good management, the desired targets will be difficult to achieve. The existence of management makes the learning system more structured. This research aims to find out how the time management program in the Tahfidz Maskanulhuffadz Medan Islamic boarding school is so that it can complete memorizing 30 juz of the Al-Quran in the span of one year. Using a qualitative research approach, this research uses. The research approach taken is a qualitative approach. namely descriptive data in the form of written words taken from Maskanulhuffadz's daily guidebook as well as information obtained from people's words and behavior that can be obtained. The data collection techniques used were through interviews, observation and copying documents. The results of this research explain the good time management of the program which has been prepared and designed to utilize one year's time. Students can complete their memorization quickly and the three year program is compressed into one year.